Study on abrasive particle impact modeling and cutting mechanism. Issue 1 (1st December 2021) - Mu, Mingfei; Feng, Long; Zhang, Qiang; Zang, Wanshun; Wang, Haixia
Abstract: Abrasive water jet impact is widely applied in processing, oil fracturing, coal mining, rock crushing, and other engineering fields. The influence of abrasive particles on cutting performance is one of the main characteristics of this technology, which is different from pure fluid cutting. Therefore, as for improving the cutting performance of abrasive water jet, studying the cutting mechanism of abrasive water jet, and clarifying the mapping relationship between particle parameters and cutting, it is of great theoretical and practical significance to clarify the impact failure mechanism and material removal mechanism of abrasive particles in the process of high‐speed impact. In order to study the effect of abrasive particles on cutting performance, irregular abrasive particles are simplified to angular particles and circular particles in this paper. The impact shooting process of particles in abrasive jet cutting is numerically simulated by using smoothed particle hydrodynamics (SPH) method, and the target impact experiments are carried out. The fracture processes of ductile materials and brittle targets impacted by different shapes of particles are studied. The results are showed as follows. Firstly, the SPH numerical model has high accuracy and successfully reproduces the collision process of particles in the process of abrasive jet cutting, including the deformation mechanisms such as plowing, cracking and crushing of the target, and the error of the dent curve formed by the collision is less than 0.5 mm. Secondly, the impact mechanism of angular and circular particles is different for targets with different material properties. For ductile materials, the process of material accumulating to failure value is slow, mainly by the way of accumulation removal. And for brittle materials, it mainly produces plastic deformation and failure, without obvious material accumulation and extrusion area. Thirdly, different impact angles of particles have great influence on material removal. Abstract : This paper mainly studies the impact mechanism of abrasive particles in the abrasive waterjet impact process in the field of energy mining.